Effect of Bismuth Ferrite (BIFEO3) Nanoparticles On Rheological and Mechanical Properties of Class G Oil Well Cement (Chemical Engineering Research Bulletin, 2023)
Oil well cement plays an important role in drilling operations. Oil well cement restricts fluid movement between the formation and supports the casing. To understand the behavior of cement slurry, we must analyze the rheological and mechanical properties of that slurry. This study investigates the effect of bismuth ferrite (BiFeO3) nanoparticles in API Class G oil well cement (OWC). In this experiment, nanoparticles of BiFeO3 are made in the laboratory using the solution evaporation method (SEM). NPs are dosed at different concentrations of 0.05, 0.1, 0.2 and 0.3% by weight of cement (BWOC) in the laboratory-prepared cement slurries. For all cement slurries, the water-cement (w/c) ratio was maintained at 0.44. The experimental work encompassed the synthesis and characterization of bismuth ferrite NPs, evaluating slurry density, specific gravity, apparent viscosity, plastic viscosity, and yield point. The result of this study reveals that 0.05, 0.2, and 0.3% BWOC concentrations of nanoparticles decreased the plastic viscosity by a maximum of 42%. Apparent viscosity of cement slurries was increased for all concentrations of nanoparticles except 0.3% BWOC and a maximum increment of 5.54% for the 0.2% BWOC. This experiment also provides an increment for the yield point of cement slurries. The yield point was increased by 6.1%, 18.5% and 23.47% compared with the base cement slurry at 0.05, 0.2 and 0.3% BWOC concentrations of nanoparticles respectively. In this study, the density and specific gravity of cement slurry dropped slightly by 4.9% and 2.08% respectively. In the compressive strength test, this NPs showed a great result and there was an increment in compressive strength for all concentrations of nanoparticles. A maximum increment of 80% was obtained at 0.3% BWOC concentration of NPs. This indicates that BiFeO3 nanoparticles can be used as a potential additive in Class G oil well cement (OWC) to enhance its rheological and mechanical properties. However, further tests should be conducted to ascertain its stability under High pressure, High Temperature (HPHT) conditions.Chemical Engineering Research Bulletin 23 (2023): 73-78